2022
DOI: 10.1021/acs.est.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

Land–Ocean Exchange Mechanism of Chlorinated Paraffins and Polycyclic Aromatic Hydrocarbons with Diverse Sources in a Coastal Zone Boundary Area, North China: The Role of Regional Atmospheric Transmission

Abstract: The marine environment is regarded as a crucial "sink" of numerous land-origin pollutants. As typical boundary regions, the coastal and offshore areas are used to evaluate the dominating transfer process and land−ocean exchange mechanism of semivolatile organic compounds. In air samples collected from a coastal area in North China over a whole year, chlorinated paraffins (CPs), including short-chain CPs and medium-chain CPs, and prior control 16 polycyclic aromatic hydrocarbons (PAHs) were determined, with mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…Most of the evidence has supported the LRAT potentials of SCCPs and MCCPs. For example, model estimations showed that SCCPs have LRAT potential, , consistent with field observations of SCCPs in the atmosphere globally. ,, Also, monitoring studies of SCCPs and MCCPs in the air from remote areas and polar environments have implied that both are subject to LRAT. , Compared to LCCPs, the existing observations indicated a tremendous LRAT potential for SCCPs and MCCPs. ,, This is because SCCPs and MCCPs have lower vapor pressure and higher volatility than LCCPs and thus are more likely to attach to particulate matter in the atmosphere. , In addition, longer-chain CPs generally have larger particle fractions. Therefore, part of MCCPs and virtually all LCCPs are limited to LRAT potential by micro- and nanoplastics, considered potential vectors for the LRAT of POPs. , This finding highlights that the atmospheric transport of CPs varies between congeners due to a wide range of physical and chemical properties (Table S1).…”
Section: Sources and Transport Of Cps In The Marine Environmentsupporting
confidence: 53%
See 3 more Smart Citations
“…Most of the evidence has supported the LRAT potentials of SCCPs and MCCPs. For example, model estimations showed that SCCPs have LRAT potential, , consistent with field observations of SCCPs in the atmosphere globally. ,, Also, monitoring studies of SCCPs and MCCPs in the air from remote areas and polar environments have implied that both are subject to LRAT. , Compared to LCCPs, the existing observations indicated a tremendous LRAT potential for SCCPs and MCCPs. ,, This is because SCCPs and MCCPs have lower vapor pressure and higher volatility than LCCPs and thus are more likely to attach to particulate matter in the atmosphere. , In addition, longer-chain CPs generally have larger particle fractions. Therefore, part of MCCPs and virtually all LCCPs are limited to LRAT potential by micro- and nanoplastics, considered potential vectors for the LRAT of POPs. , This finding highlights that the atmospheric transport of CPs varies between congeners due to a wide range of physical and chemical properties (Table S1).…”
Section: Sources and Transport Of Cps In The Marine Environmentsupporting
confidence: 53%
“…By contrast, the lower concentrations of ∑CPs appeared in the particle samples (1.72–44.9 ng/m 3 ), with C14 and Cl9–10 congeners as the predominant compounds. Given the season, higher concentrations of ∑gCPs (gaseous CPs) and ∑pCPs (particle CPs) were found in summer and winter than in other seasons in Chinese coastal areas, which may be because a lower ambient temperature made less evaporation of CPs to the gas phase, leading to the condensation of CPs onto the particle phase in winter . Seasonal variations were also observed in Liaodong Bay, China, where higher concentrations of ∑CPs occurred in the summer (range of 8.3–39 ng/m 3 , mean of 24 ng/m 3 ) than in spring (range of 3.8–13 ng/m 3 , mean of 6.9 ng/m 3 ) in the gas phase of air samples.…”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides, the higher temperatures in the summer season might maximize the volatilization of CPs compared to the winter season. This was consistent with a previous study that the mean values of log K p were −2.12 and −2.52 in cold and warm seasons for CPs . In addition, other environmental conditions, such as moisture content and/or light intensity, could also influence the behavior of CPs in the STP.…”
Section: Resultssupporting
confidence: 94%